Value and the Humanities The Neoliberal University and Our Victorian Inheritance - Bulaitis, Zoe Hope (Palgrave Studies in Literature, Culture and Economics, 2020)
Tracing the shift from liberal to neoliberal education from the nineteenth century to the present day, this open access book provides a rich and previously underdeveloped narrative of value in higher education in England. Value and the Humanities draws upon historical, financial, and critical debates concerning educational and cultural policy. Rather than writing a singular defence of the humanities against economic rationalism, Zoe Hope Bulaitis constructs a nuanced map of the intersections of value in the humanities, encompassing an exploration of policy engagement, scientific discourses, fictional representation, and the humanities in public life. The book articulates a kaleidoscopic range of humanities practices which demonstrate that although recent policy encourages higher education to be entirely motivated by outcomes, fiscal targets, and the acquisition of employability skills, the humanities continue to inspire and aspire beyond these limits. This book is a historically-grounded and theoretically-informed analysis of the value of the humanities within the context of the market.